1998
DOI: 10.1557/jmr.1998.0064
|View full text |Cite
|
Sign up to set email alerts
|

Thermal transport due to material and gas flow in a furnace for drawing an optical fiber

Abstract: The transport processes involved in the neck-down region for optical fiber drawing are numerically investigated. In this manufacturing process, a moving glass rod is heated in a furnace containing an inert gas environment and drawn into a thin optical fiber. The conjugate problem is solved considering both radiation and convection, with focus on the latter. Two different flow configurations, involving inert gas flow in the same as well as in the opposite direction as the moving preform/fiber, are considered in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Too high draw tension may cause the fiber breakage, or, if it is too low, it could be the source of undesirable fiber vibration and process instability in the continuous drawing process. The strength of draw tension recommended in fiberoptics industries is known to be on the order of 100 g or 1 N. By considering the force balance between draw tension and viscous and gravitational forces, Yong Ki Kim, Choi, Kwak and Kyoungjin Kim, Journal of Thermal Science and Technology, Vol.12, No.2 (2017) draw tension acting on the drawn glass fiber or preform at a given arbitrary z location can be evaluated as (Choudhury and Jaluria, 1998) …”
Section: Calculation Of Fiber Draw Tensionmentioning
confidence: 99%
See 2 more Smart Citations
“…Too high draw tension may cause the fiber breakage, or, if it is too low, it could be the source of undesirable fiber vibration and process instability in the continuous drawing process. The strength of draw tension recommended in fiberoptics industries is known to be on the order of 100 g or 1 N. By considering the force balance between draw tension and viscous and gravitational forces, Yong Ki Kim, Choi, Kwak and Kyoungjin Kim, Journal of Thermal Science and Technology, Vol.12, No.2 (2017) draw tension acting on the drawn glass fiber or preform at a given arbitrary z location can be evaluated as (Choudhury and Jaluria, 1998) …”
Section: Calculation Of Fiber Draw Tensionmentioning
confidence: 99%
“…Paek and Runk (1978) and Paek (1999) established a one-dimensional momentum balance model for the prediction of preform neck-down profile but the effects of purge gas in draw furnace was treated simply by prescribing convective heat transfer coefficient estimated from the experimental data. Also, there have been multi-dimensional computational investigations on glass fiber drawing by considering the convective transport of purge gas around the preform neck-down shapes which profiles were taken from the measurements (Lee and Jaluria, 1997;Choudhury and Jaluria, 1998;Yan and Pitchumani, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the equations are coupled because of property variation and viscous dissipation. For the convenient implementation of the finite difference method, the flow domains for the glass and purge gas are transformed into cylindrical ones [15,19]. The boundary conditions for a free surface, arising from the force balance, are employed here at the interface between the glass and the purge gas in order to determine the neck-down profile.…”
Section: Analysis and Numerical Solutionmentioning
confidence: 99%
“…They studied a 5cm diameter preform and it was shown that the glass velocity distribution is close to 1D while the glass temperature has a 2D distribution. Other 2D studies include Lee and Jaluria [7], Choudhury and Jaluria [8], Yin and Jaluria [9] and Cheng and Jaluria [10]. The above studies only considered the furnace domain, and have based on either one of the two assumptions; the fiber solidifies within the furnace, or an arbitrary glass diameter is specified at the furnace exit.…”
Section: Proceedings Of Ht-fed04mentioning
confidence: 99%